Handbook of adhesives and surface preparation : technology, applications and manufacturing - Ebnesajjad, Sina. (Amsterdam : William Andrew/Elsevier, 2011)
Provides a practical survey of all aspects of adhesives technology, from selection and surface preparation to industrial applications and health and environmental factors. The handbook focuses on the applied aspects of adhesives selection and applications, and it provides practical techniques for rendering materials surfaces adhearable. Particular attention is given to adhesives applications in the automotive, aerospace, medical, dental and electronics sectors.
Introduction and adhesion theories -- Introduction to surface preparation and adhesion -- Surface tension and its measurement -- Surface and material characterization techniques -- Material surface preparation techniques -- Surface preparation of metals -- Surface preparation of thermoplastics, thermosets, and elastomers -- Characteristics of adhesive materials -- Heat-resistant adhesives -- UV-radiation curing of adhesives -- Adhesives for special adherends -- Adhesives for electronics -- Adhesives for aerospace structures -- Adhesives for medical and dental applications -- Adhesion promoters.
Includes bilbiographical references and index.
Keywords: Adhesives; Adhesion; Dental adhesives